2016
DOI: 10.21037/tgh.2016.11.06
|View full text |Cite
|
Sign up to set email alerts
|

Historical assumptions of lymphadenectomy

Abstract: The role of lymphadenectomy for the treatment of gastric cancer is still very much open to debate. Consequently, Japanese, European and American surgeons perform different typologies of lymphadenectomy because of the absence of randomized clinical trials confirming the superiority of extended lymphadenectomy over less invasive surgery. In Japan, D2 lymphadenectomy has been considered as the gold standard for advanced gastric carcinoma for many years. Although numerous European studies have been conducted in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This result was also registered in Huang et al's 3 series in which authors reported that 84% of D2 were performed during the learning curve versus 97% after its completion (p = 0.046). In our centers, we have always supported the D2 lymphadenectomy also for early gastric cancer, [22][23][24] except for selected patients as reported in the guidelines. 9 In our series, patients' selection might have been different in the two periods, as in P2 the cohort could represent the ideal candidate for RG and D2 lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…This result was also registered in Huang et al's 3 series in which authors reported that 84% of D2 were performed during the learning curve versus 97% after its completion (p = 0.046). In our centers, we have always supported the D2 lymphadenectomy also for early gastric cancer, [22][23][24] except for selected patients as reported in the guidelines. 9 In our series, patients' selection might have been different in the two periods, as in P2 the cohort could represent the ideal candidate for RG and D2 lymphadenectomy.…”
Section: Resultsmentioning
confidence: 99%